Pengembangan Modul Pembelajaran Biologi Berbasis Hots (Higher Order Thinking Skills) pada Materi Sistem Reproduksi - M.Ilham Ramadhan; Indayana Febriani Tanjung; Reflina (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This study aims to determine the level of validity, practicality and effectiveness of biology modules based on HOTS (Higher Order Thinking Skills) on the material of the human reproductive system. This research is a 4-D model of R&D (Research and Development) (Define, Design, Development, and Disseminate). The subjects of the trial conducted in the study consisted of 20 students from class XI-MIA-2 at SMA Negeri 6 Medan. The results showed that the percentage of module validity scores from material experts was 84% ​​with a very valid category. and module experts by 100% with the